Macroskyttea parmotrematis gen. et sp. nov. (Helotiales, Leotiomycetes, Ascomycota), a new lichenicolous fungus from Bolivia - Etayo, Javier; Flakus, Adam; Suija, Ave; Kukwa, Martin (Phytotaxa, 2015)
A new genus and species of lichenicolous fungi, Macroskyttea parmotrematis, inhabiting thalli of Parmotrema aberrans and P. ultralucens, is described from montane forests in Bolivia. The new genus is similar to Skyttea and Diplolaeviopsis from which it clearly differs in larger apothecia with widely exposed black pigmented discs, macroscopically easily visible long excipular hairs covering the whole exciple, and different ascus structure. Our results based on Maximum Likelihood (ML) and Bayesian analysis of three loci (nuSSU, nuLSU and 5.8S of the ITS) suggest that the new genus belong to Helotiales and is sister to Diplolaeviopsis ranula within encoelioid-clade. The conidial-ascosporic connection of Diplolaeviopsis ranula is shown here based on the nucleotide match of rDNA sequences.